The relationship between smartphone addiction and depression among university students in Karachi: a cross-sectional study - Abid, Ubaidullah; Khan, Tooba Jawed; Sheikh, Asif; Saleem, Saud; Kayani, Hammad Afzal; Habib, Muhammad Atif (International Journal Of Community Medicine And Public Health, 2020)
Background: Pakistan demographic and health survey (PDHS) estimated extensive ownership of cell phones in Pakistan with 94.7% in the urban population. Pakistan Advertiser Company reported 77 % of cell phone users aged between 21-30 years. Although, no research was conducted with university population for addiction and depression, so this study aims to find the link between Smartphone addiction and depression in SZABIST University students of Karachi, Pakistan. Methods: Cross-sectional study was conducted with self-assessment tools, comprised of three sections: socio-demographic information, smartphone addiction scale-short version (SAS-SV) and Beck’s depression inventory-II (BDI-II). Responses for SAS-SV were rated on a 6-point Likert scale and BDI-II was summated on range 0-60. Percentages mean score was commuted for SAS-SV; the mean score was computed and categorized for BDI-II. Descriptive statistics and regression analysis were used for data analysis. Statistical significance was set at p<0.01. Results: Total participants were N=225, of which 140 (62.2%) were males and 85 (35.8%) were females. The mean±SD of their ages were 20.9±2.9. Age was found insignificant with depression after applying multiple linear regressions. Mean score of SAS-SV was 54.8±17.2, and BDI-II was13.4±9.6, which showed a significant positive association (OR, 0.241; 95% CI, 0.2 to 0.3; p<0.001). Prior adjusting coefficient, males were speculated having a higher level of depression. Conclusions: A significant positive correlation was found between Smartphone addiction and depression, among University Students of SZABIST. Control smartphones usage is advised for undergraduate students as they are more prone to depression compared to postgraduate students.